Mental (dis)order in later Medieval Europe - Katajala-Peltomaa, Sari; Niiranen, Susanna (Later medieval Europe, 2014)
"Mental (Dis)order in the Late Middle Ages sketches the boundaries between mental, social and physical order and various states of disorder -- unexpected mood swings, fury, melancholy, stress, insomnia, and demonic influence -- and focuses on the interaction between lay and elite cultures"--Provided by publisher